دراسة تصنيفية لجنس L. Medicago (فصيلة Fabaceae Lindl.) في محافظة اللاذقية باستخدام معايير مورفولوجية وتشريحية - مخول, جرجس; الصالح العبد, بسام (Latakia University Journal -Biological Sciences Series, 2018)
تشكل محاولات البحث عن معايير جديدة للتمييز بين الوحدات التصنيفية ، واحدة من مهام علم التصنيف النباتي ، كما تعد دراسة الغطاء النباتي ، وتحديد مناطق انتشار الأنواع في سورية مهمة ملحة وهامة نظراً لقلة الدراسات المتخصصة في هذا المجال ، خاصة تلك المنجزة بواسطة الخبرات المحلية وبلغتنا العربية ∙ وقد أظهرت دراسة أنواع جنس الفصة Medicago L. في 25 موقعاً في محافظة اللاذقية وجود 18 نوعاً تمثل جميع تحت الأجناس الأربعة التابعة للجنس المذكور، منها خمسة أنواع سجلت للمرة الأولى في المحافظة ، وهذا يشكل 20% تقريباً من عدد أنواع الجنس كاملة ، مما يدل فعلاً على أن محافظة اللاذقية تشكل مركزاً مهماً للتنوع الوراثي والانتشار الجغرافي لأنواع هذا الجنس∙ وقد بينت دراسة توزع المسامات وتركيب الجهاز المسامي أن المسامات عند جميع الأنواع توجد على وجهي الورقة العلوي والسفلي (Amphistomatic)، وأن نمط الجهاز المسامي السائد لديها جميعاً Anisocytic ، Anomotetracytic ، Anomocytic، Isotricytic ، Staurocytic ، ونادراً Paracytic ، مما يجعلها مبدئياً سماتاً قليلة الأهمية من الناحية التصنيفية للتمييز بين هذه الأنواع ∙ The attempts of this search for new criteria for differentiating between the taxa are considered as one of the tasks of the plant taxonomy, this study of the plants and the places where they are found is an urgent and important one in Syria, because few specialized studies are available especially those done locally in Arabic. this study of Medicago species in 25 places in Lattakia shows that there are 18 species which presents the 4 subgenus of Genus Medicago. Five of which have been recorded for the first time in Lattakia. This species form nearly 20 % of the total number of the genus’s species. This asserts that Lattakia is an important center of genetic diversity and geographical distribution of this species. this study of the stomata and the structure of the stomatal complex shows that the stomata occurs on both surfaces of the leaf (Amphistomatic). It also shows that the ascendant types of the stomatal complex seen in all species are mainly Anisocytic, Anomotetracytic, Anomocytic, and Isotricytic, Staurocytic, and rarly Paracytic. The above criteria have little importance for Taxonomy and to distinguish between these species.